RESPONS DOSIS DAN INTERVAL WAKTU APLIKASI KOMPOS Azolla pinnata TERHADAP PRODUKTIVITAS TANAMAN KACANG PANJANG (Vigna sinensis L.) - Elrisa Ramadhani; Refnizuida; M. Lisman Puja Kesuma (Agrica Ekstensia, 2020)
Long bean plant is one of the horticultural crops that can be developed an environmentally friendly organic farming system. This study aimed to determine the effect of time intervals and doses of Azolla compost on the productivity of long bean plants (Vigna sinensis L). This research was conducted from January to March 2015 in Dusun XVI Percut Village, Percut Sei Tuan sub-district, Deli Serdang Regency. The research method was a factorial randomized block design with 2 factors, 3 replications, and 16 treatment combinations. The first factor was time interval for applying Azolla compost were at planting, 1 week after planting, 2 week after planting and 3 week after planting, and the second factor was Azolla compost dose, were 0, 5 kg; 1 kg; 1.5 kg and 2 kg of Azolla compost / Plot. The plot area used is 1 m2. The interaction between the treatment of the influence of time intervals and the dosage of Azolla compost showed no significant effect on all observation parameters. The results showed that the time interval of applying Azolla had a significant effect on plant height of 5 WAP, number of branches, sample production, and plot production, but had no significant effect on the age of flowering plants, while the difference in dose had a significant effect on plant height of age of 5 MST, number of branches, production sample, and plot production, but no significant effect on flowering age. Azolla treatment at planting showed better results, with the production per sample about 414.04 g. Application of Azolla with a dose of 1.5 kg Azolla compost / Plot can give better results on the productivity of long bean plants, with the production per sample about 419.56 g.